AB0976 Associations between ultrasonographic and radiographic features of osteoarthritis and pain – a within-person knee-matched case-control study. (23rd January 2014) - Haugen, I.K.; Mathiessen, A.; Engen, C.N.; Robinson, P.S.; Østerås, N.; Øiestad, B.E.; Engebretsen, L.; Hammer, H.B.; Kvien, T.K.
Abstract : Background: Associations between osteoarthritis (OA) features and pain are difficult to study due to varying pain report between persons. A study using a within-person knee-matched design showed strong associations between radiographic knee OA and pain (1). Few studies have investigated the associations between ultrasonography (US) features of knee OA and pain. Objectives: To investigate whether US features and radiographic knee OA were associated with pain using a within-person knee-matched design. Methods: Eligible participants were those with knee pain (mild/moderate/severe) in one knee but not in the contralateral knee during the last week. We included 40 participants (27 women, mean (SD) age 63.5 (8.8) years) from the MUST study, which is a population-based study of persons with self-reported OA. The US exam included assessment of osteophytes (grade 0-3) at medial/lateral femur/tibia, cartilage thickness (millimetres) at the apex of medial femoral condyle, impaired cartilage quality (grade 0-2), synovitis (grade 0-3) and meniscal protrusion (grade 0-2). All US features except cartilage thickness were dichotomised as absent/present prior to analyses. Radiographic knee OA was defined as Kellgren-Lawrence grade (KLG)≥2 (0-4 scale). We examined the relation of each OA feature (exposure) to knee pain (outcome) by conditional logistic regression due to the matched nature of the data. To be able to estimate the effect of the exposure, there must be variation of the exposure within the matched set. Hence, only those with OA feature in one knee and not in the contralateral knee are informative. Due to within-person matched design, the effects of confounders at person level are eliminated. Results: Twenty-eight participants had self-reported knee OA. Unilateral knee pain was present in all participants of which the majority reported mild pain (n=26). Twelve persons had US-defined osteophytes in the painful knee only, whereas three persons had osteophytes in the non-painful knee only (representing informative matched sets), and the association between osteophytes and pain was statistically significant. A strong and significant association was also found between radiographic OA and pain (table). Conclusions: Radiographic knee OA was strongly associated with pain in this within-person knee-matched case-control study although the sample was small. We found that US-detected OA pathology, such as cartilage assessment and synovitis, was in less degree associated with knee pain, and significant associations were found for osteophytes only. These results may perhaps question the validity and usefulness of US in explaining pain in knee OA. References: Neogi T. BMJ 2009;339:2844 Disclosure of Interest: None Declared